FUTURE CITY PLANNING POLICIES: VISION OF THREE CITY LEADERS - Dwidayati, Kunthi Herma; Barliana, Mokhamad Syaom Barliana Syaom; Rahmanullah, Fauzi; Mardiana, Riskha; Adhi, Nuryanto (LANGKAU BETANG: JURNAL ARSITEKTUR, 2026)
The broad goal of urban governance, is the ability to address issues of equality, livability and sustainability in the cities of the future. In addition, city development is also expected to become larger and more numerous, with much more complex problems such as social inequality, lack of infrastructure, mobility issues, high population density, etc. Based on those urban issues, the equality, livability and sustainability in future cities also have not yet been reflected in the implementation of governance in most cities in Indonesia. Therefore, this research aim is to compare the visions of leaders of three cities: Bandung, Semarang and Denpasar in architectural policies for urban planning with a future perspective. The research method uses quantitative content analysis of city leaders' vision and policy documents in urban planning. The study systematically identifies key indicators embedded within each city’s strategic direction. The comparative analysis is further strengthened through qualitative interpretation, enabling a deeper understanding of how each city conceptualizes long term urban transformation, spatial quality and sustainable development. Through this mixed analytical approach, the study provides insights into the similarities, differences and unique priorities that characterize future oriented urban governance in the three cities.